Membangkitkan Kembali Destinasi Wisata (Pelatihan Bagi Pengelola Kampung Wisata Lawas Maspati) - Dian Reindrawati; Upik DE Noviyanti; Nur E Suriani (Forum Kerjasama Pendidikan Tinggi, 2020)
The purpose of this activity is to provide awareness to tourism managers related to tourism conditions in the pandemic era, what to do and how to improve the ability of the managers of the Maspati Surabaya Lawas Tourism Village to survive in the pandemic era. This is important considering that the managers of the Maspati Surabaya Lawas Tourism Village really need knowledge and information about what the tourist destinations must do to be able to survive in the pandemic era. It is hoped that the knowledge and skills gained after the training will increase the manager's provision and knowledge.